Optical and Morphology Properties of Cu2Se at Different Temperatures by Thermal Evaporation - Hadi , Shaimaa M.; Al-Maiyaly , Bushra K.H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
A low-cost thermal evaporation deposition technique has been used for the preparation of Cu2Se thin films on glass substrates at RT with a thickness of 500 nm. Structural and optical properties of these films were investigated. Structural characterization of the films was done using X-ray diffraction XRD analyses, atomic force microscopy AFM was used for the morphological characterization of the film samples, and UV-Vis spectroscopy was also used for the characterization of the samples. The films have been treated at different temperatures (403, 453 &503) K for 1 hour. X-ray diffraction (XRD-with wavelength 1.54 A) study of these films suggests a cubic structure and has prominent (220) orientation. And AFM analysis, it is evident that Cu2se films are polycrystalline, and that crystallite size and average grain size for films after annealing were increasing. The optical absorption coefficient (α) of the films was determined from absorbance spectra in the range of wavelengths (400-1100) nm. The deposited films showed transmittance (∼18%) and a direct band gap of about 2.2 eV. The structure and the optical properties of the films may find practical applications in the field of renewable energy